Clinicodemographic profile and treatment outcomes of COVID-19 patients admitted in a designated tertiary care hospital, Chennai: A comparative analysis of first and second wave of the pandemic - Sivagurunathan Chinnaian; Recharla Chenchu Karthik; Ezhilvanan Mani; Vikram Ashokkumar; Aarthi Saravanan (Asian Journal of Medical Sciences, 2023)
Background: COVID-19 caused by severe acute respiratory syndrome (SARS)-COV 2 virus was declared a pandemic by the WHO in March 2020. India has reported 44,689,512 cases and 530,779 deaths as of March 9, 2023. Different variants may lead to varying clinical presentations and outcomes, emphasizing the need for ongoing analysis of local COVID-19 patients. Aims and Objectives: To describe the clinic-demographic profile and treatment outcomes of COVID-19 patients in a tertiary care hospital in Chennai and to compare the patient characteristics during the first two waves of the pandemic in India. Materials and Methods: A retrospective record-based study analyzed patients with SARS-CoV-2 between May 2020 and July 2021, collecting data on demographics, travel history, symptoms, hospital stay, and outcome. Data were analyzed using SPSS Version 20.0. Chi-square test and Fisher exact tests were used to ascertain significant association between variables. Results: Out of 944 cases of COVID-19, 70% were aged 20–60 years with a male predominance in both waves. The mean age during the first wave was 45.04±17.32 and during the second wave was 45.86±15.49. Intensive care and ventilatory support needs increased in the second wave. Hospital stay was longer during the first wave. Death rates were 3% and 14% in the first and second waves, respectively. Conclusion: In our study, community transmission was observed as most COVID patients did not have travel history. Males, elderly and those with comorbidities were heavily impacted. The second wave had higher ICU and mortality rates.